Design and Modellingof a Pneumatic Vice Machine - Talemwa, Prosper (Kabale University, 2024)
This study presented the design and development of a pneumatic vice engineered to deliver a stable clamping force exceeding 500N, suitable for a variety of industrial applications. The design focuses on optimizing the pneumatic actuator mechanism to ensure consistent performance under varying load conditions. Key features include a robust frame constructed from high-strength materials, an adjustable clamping jaw system for accommodating different workpiece geometries, and integrated pressure control for fine-tuning clamping force. Additionally, the vice incorporates safety mechanisms to prevent over-clamping and enhance operator safety. Through a series of experiments, the vice's performance was evaluated, demonstrating its reliability and effectiveness in maintaining the desired clamping force during machining and assembly processes. The results indicate that this pneumatic vice can significantly improve productivity and precision in manufacturing environments. Future work will explore the integration of automation and sensor technologies to further enhance its capabilities. The general objectives of this project were to design and simulate an efficient and easy-to-operate pneumatic Vice and specific objectives were to determine the design parameters of the pneumatic vice, design using 3D modeling software (DS SOLIDWORKS), sizing, and select the components of the pneumatic vice, the design the layout of the pneumatic vice, simulation using ANSYS software and fabricating the system using suitable selected materials and techniques basing on design specifications. The methods included library searches, field surveys, internet searches, and interviews. Reviewing design parameters of different scholars to come up with the conceptual design and developing the layout by use of SOLID WORKS. The design for different major components was carried out while others were just selected. Stress analysis and simulations were also performed to study the behavior of the jaws.